Trimming the fat of beef production: the transportation of ranching - Hazelton, Scott Anthony (Kansas State University, 2020)
Transportation is a crucial portion of an agricultural producer’s daily activities. Agricultural products require many miles to produce, both from direct producers and from outside contractors. This research thesis analyzes the daily travel of a ranch using GPS trackers installed into the ranch’s vehicles. The most significant finding is the high percentage of idling, over 29.9 percent of engine use. The ranch used over 4,700 gallons of fuel at idle resulting in over $10,000 in fuel wastes and 52.8 tons of carbon dioxide emitted. Metrics were developed for further evaluation and regional comparisons of ranch work. The metrics show the cow to miles ratio, acre to miles ratio and the stocking ratio to miles per acre. These metrics were created to show the efficiency of the ranch’s travel on a yearly basis and for comparison between different ranches. Recommendations were given to the rancher to limit their idling, such as habitual and technological changes, and reduce their vehicle-miles traveled and travel time by chaining trips, diversifying their fleet and changing routing decisions to save miles and drive time. This study provides a base for further study into the daily transportation of agriculture, a base data set has been created and more data is needed to compare ranches to one another.
Keywords: Sustainable Agriculture; Transportation